The EHD protein Past1 controls postsynaptic membrane elaboration and synaptic function. - Koles, K.; Messelaar, E.M.; Feiger, Z.; Yu, C.J.; Frank, C.A.; Rodal, A.A. (Molecular Biology of the Cell, 2015)
Membranes form elaborate structures that are highly tailored to their specialized cellular functions, yet the mechanisms by which these structures are shaped remain poorly understood. Here, we show that the conserved membrane-remodeling C-terminal Eps15 Homology Domain (EHD) protein Past1 is required for the normal assembly of the subsynaptic muscle membrane reticulum (SSR) at the Drosophila melanogaster larval neuromuscular junction (NMJ). past1 mutants exhibit altered NMJ morphology, decreased synaptic transmission, reduced glutamate receptor levels, and a deficit in synaptic homeostasis. The membrane-remodeling proteins Amphiphysin and Syndapin colocalize with Past1 in distinct SSR subdomains and collapse into Amphiphysin-dependent membrane nodules in the SSR of past1 mutants. Our results suggest a mechanism by which the coordinated actions of multiple lipid-binding proteins lead to the elaboration of increasing layers of the SSR and uncover new roles for an EHD protein at synapses.